Kepastian Hukum Penerapan Doktrin Business Judgement Rule terhadap Keputusan Direksi Badan Usaha Milik Negara (BUMN) dalam Perkara Tindak Pidana Korupsi - Andi Naser; Kristiawanto Kristiawanto; Maryano Maryano (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
State-Owned Enterprises (SOE) cannot be separated from the role of the board of directors. However, decisions made by directors in good faith and with due care are frequently drawn into the realm of criminal law whenever state financial losses occur. In fact, losses in the business context do not necessarily constitute negligence or abuse of authority as stipulated under the Anti-Corruption Law, but may instead result from ordinary business risks or business losses. In this context, the Business Judgment Rule (BJR) doctrine emerges as a form of legal protection for directors, aimed at preventing the criminalization of bona fide business decisions. This research aims to examine the form of criminal liability of BUMN directors in corruption cases in Indonesia and to analyze the extent of legal certainty in the application of the Business Judgment Rule doctrine to decisions made by BUMN directors in corruption cases. The research employs a normative juridical legal research method. It applies several approaches, namely the statutory approach, conceptual approach, comparative approach, and case approach. The findings indicate that in the application of the Business Judgment Rule doctrine to decisions made by BUMN directors in corruption cases, directors’ decisions should not be subject to legal challenge, as the governance of BUMN corporate organs remains governed by the Company Law and the State-Owned Enterprises Law. Consequently, state losses arising from directors’ business decisions cannot be attributed to personal criminal liability. If shareholders—represented by the state—consider themselves to have suffered losses, legal remedies may be pursued through civil litigation by filing a claim before the court. As a recommendation, this study emphasizes the need for comprehensive regulations governing the application of the Business Judgment Rule doctrine in practice, in order to minimize disparities in judicial decisions and to ensure legal certainty for directors in their efforts to generate value and benefits for the corporation